Educating for Success: A Program to Enhance the Self Concept of Freshmen on a Large College Campus: An Evaluation - Swell, Lila (Canadian Journal of Higher Education, 1992)
A pre/post analysis of 6 instruments administered over 2 semesters for EFS* vs control group Freshmen students revealed that the EFS program was effective in increasing positive self attitudes.